Chapter La production d'alun en Occident: l'essor d'une industrie nouvelle à la fin du XVe siècle - Boisseuil, Didier (Datini Studies in Economic History, 2023)
This article explores the conditions under which alum production has developed in the Western Mediterranean, in the second half of the fifteenth century. In two decades, between about 1460 and 1480, several important production sites have appeared in the Italian peninsula or in the Iberian peninsula. They have provided European industries and crafts with quality alum, and they quickly overshadowed sources of supply, that had previously prevailed in Anatolia or the Aegean Sea. The article discusses the useful knowledge mobilized to facilitate this growth, in particular, the techniques used and the players involved in this changeover.